Doing business electronically : a global perspective of electronic commerce - Sudweeks, Fay.; Romm, Celia T., 1954- (London ; New York : Springer, 1998)
Doing Business Electronically examines the major issues involved in using electronic commerce. It focuses on general, commercial, social, and cultural (rather than technical) aspects, and addresses central topics such as the implications of real-time transactions for financial institutions; how to address issues of integrity and security; how networked communities can benefit from global collaborative systems; and the implications of multimedia technology for next-generation marketing. Written for final year undergraduate and graduate students in electronic commerce and computer mediated communication, this volume will also provide invaluable supplementary reading material for courses in business information technology, information systems, organisational change and project management.
11. Design of Electronic Data Interchange Systems for Small/Medium Enterprises / Rob MacGregor, Deborah Bunker and Philip Waugh -- 12. Paying for Goods and Services in the Information Age / Boon-Chye Lee -- 13. Channel Integration / Kristeen Gleason and Dan Heimann -- 14. Information Systems for Electronic Banking / Celia Romm and Farida Peranginangin -- 15. Use of EDI at BHP Steel / Karl Rommel.
Includes bibliograhical references and index.
Keywords: Electronic commerce; Electronic data interchange